Covid-19: Good vs. Evil Dichotomy in News Media - Wardani, Agista; Adityo, Adityo (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Dichotomy may be expressed through the languages used on social media. When it comes to Covid-19, a pandemic that began in 2020, the global population is still unfamiliar with the problem and is in the process of adapting through various ideologies and strategies represented on social media. The objective of this research is to identify the dichotomy that surfaced during COVID-19 based on five reports from three YouTube channels. Qualitative discourse analysis was used by the researchers. This research focuses on the opinions of netizens on five reports that were posted on three YouTube channels about COVID-19 between January and May 2020, when Indonesia was enacting a